Sodium hyaluronate instillation in radiation-induced hemorrhagic cystitis in a patient with prostate cancer: a case report - Carcasi-Laura, Edgar Alfredo (2021)
In patients with prostate cancer, radiation therapy has indications as a primary, adjuvant, and rescue treatment. Radiation-induced hemorrhagic cystitis is one of the most serious complications in the toxicity of patients with some type of pelvic cancer. We have a patient who, after undergoing radical prostatectomy plus lymphadenectomy, underwent adjuvant radiation therapy in 2015. In January 2020, he presented with radiation hemorrhagic cystitis, entering the hospital where he received bladder irrigation and cystoscopic fulguration. After his medical discharge, he underwent instillations with sodium hyaluronate with satisfactory results.